2002
DOI: 10.1099/0022-1317-83-5-1237
|View full text |Cite
|
Sign up to set email alerts
|

Mutant prion protein acquires resistance to protease in mouse neuroblastoma cells

Abstract: Conversion of the cellular isoform of the prion protein (PrP C ) into the pathogenic isoform (PrP Sc ) is thought to be the causative event in prion diseases. Biochemically, PrP Sc differs from PrP C in its partial resistance to proteinase K (PK). The amino acid sequence AGAAAAGA, comprising residues 112-119 of the murine PrP C , has been shown to be amyloidogenic and evolutionarily conserved. To assess the effect of mutations at and around this hydrophobic sequence on protease resistance, the sequence was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
1
19
1
Order By: Relevance
“…In contrast, C39 displayed partial α-cleavage inhibition in both Hpl and HeLa cells, which is in agreement with the finding that a mutant bearing a deletion of the region 114–121 is inefficiently cleaved in the brain of transgenic mice [14]. We conclude that, in contrast to published claims [19], the substitution of the palindrome with a total or partial polyglycine chain does not have a measurable impact on α-cleavage of PrP C .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In contrast, C39 displayed partial α-cleavage inhibition in both Hpl and HeLa cells, which is in agreement with the finding that a mutant bearing a deletion of the region 114–121 is inefficiently cleaved in the brain of transgenic mice [14]. We conclude that, in contrast to published claims [19], the substitution of the palindrome with a total or partial polyglycine chain does not have a measurable impact on α-cleavage of PrP C .…”
Section: Resultssupporting
confidence: 89%
“…2A). A previous study reported that substitution of all palindromic glycines with alanines, as in construct BOM9, abrogated C1 generation in N2a cells [19]. We therefore assessed the cleavability of BOM9 and of BOM11, which bears only three palindromic alanine substitutions, in Prnp −/− Hpl cells [25] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…36,37 Moreover, the peptide segment 112-119 has been reported to be essential for the replication of the TSE agent in tissue cultures. 38,39 Altogether, these results indicate that membrane-associated forms of PrP C may be involved in the amplification of the TSE agent or its pathology, and that the conformational transition of PrP C to PrP Sc might be a membrane-associated process. [40][41][42] …”
Section: Introductionmentioning
confidence: 93%